Performance and Sustainability of Halal Food Smes - Rina Sari Qurniawati; Yulfan Arif Nurohman (Journal of Finance and Islamic Banking, 2021)
This study investigates the performance and sustainability of halal food SMEs in the FinTech era. The large aggregate contribution of SMEs does not yet reflect good performance in domestic and foreign market competition due to lack of financial literacy. FinTech can support financial literacy so performance and sustainability SMEs will increase. Consequently, testing the effect of fintech and literacy on the performance and sustainability of MSMEs. A total of one hundred respondents are selected using the quantitative method as sources of data collection. The questionnaires are distributed using a purposive sampling method in Surakarta, Indonesia. The software used for analysis is SEM-PLS. Â The results of this study state that the performance and sustainability of SMEs are influenced by FinTech and financial literacy